1995
DOI: 10.12693/aphyspola.88.833
|View full text |Cite
|
Sign up to set email alerts
|

GaN Synthesis by Ammonothermal Method

Abstract: It is shown that ammonothermal method can be successfully used to synthesize GaN powder of good crystallographic quality from ammonia solution at high pressure and a moderate temperature. The size of obtained GaN powder grains was of a few micrometers. The improvement of the powder crystalline quality (examined by X-ray rocking curve, scanning electroii microscopy and luminescence measurements) with increasing molar proportion of mineralizer was observed. It was therefore possible to conclude that high molar p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
69
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(80 citation statements)
references
References 0 publications
2
69
0
1
Order By: Relevance
“…(8)(9)(10) Despite the advantage of scalability over its counterparts, not many research institutes have attempted ammonothermal growth because the growth rate is relatively low, and high-pressure ammonothermal reactors are not commercially available. Since Dwiliński et al demonstrated bulk GaN with excellent crystal quality, (11) ammonothermal growth has drawn increasing attention from the nitride research community.…”
Section: Introductionmentioning
confidence: 99%
“…(8)(9)(10) Despite the advantage of scalability over its counterparts, not many research institutes have attempted ammonothermal growth because the growth rate is relatively low, and high-pressure ammonothermal reactors are not commercially available. Since Dwiliński et al demonstrated bulk GaN with excellent crystal quality, (11) ammonothermal growth has drawn increasing attention from the nitride research community.…”
Section: Introductionmentioning
confidence: 99%
“…In ammonothermal method used by us the chemical reaction takes place in highly active supercritical medium [2]. This fact allows to expect that temperature and pressure demands for GaN crystallization by this method would be much lower than in HNP technique.…”
Section: Introductionmentioning
confidence: 99%
“…If the substrate shows tilt boundaries, even if it is a native substrate but grown itself on a foreign substrate, the tilt boundaries will appear in the grown material, too [10,[37][38][39][40][41][42]. High quality of the substrate is very important, since it allows the production of more devices per substrate and devices made of low-defect-density GaN or AlN promise longer working periods at higher power without breakdown [43].…”
mentioning
confidence: 99%